PENGARUH DIMENSI FRAUD DIAMOND TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA JURUSAN AKUNTANSI - Novi Darmayanti; Isnaini Anniswati Rosyida; Galuh Adi Irawan (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2020)
This study aims to determine the influence of pressure, opportunity, rationalization, ability on academic cheating behavior of students majoring in accounting both partially and simultaneously. This research uses quantitative research methods with the type of survey research. The analysis technique used in this study is the data quality test, the classic assumption test, multiple linear regression and hypothesis testing using the t test to test the effect of variable X with partial Y variable and F test to test variable X on variable Y simultaneously with significant values 0.05% (5%). Based on the results of the study indicate that the value of the independent variables simultaneously (together) affect the dependent variable, namely academic cheating behavior (Y). Partially, the pressure variable does not have a significant effect on academic cheating, opportunity has a significant effect on academic cheating, rationalization has a significant effect on academic cheating, ability has a significant effect on academic cheating behavior.